Collaborative critical mathematics in a flipped classroom effects on students' mathematical disposition and thinking skills - Hilario, Eric Lloyd P.
The present study examined the impact of collaborative critical mathematics in a flipped classroom (CCMFC) on students’ mathematical disposition—focusing on aspects such as confidence, flexibility, usefulness, perseverance, curiosity, and metacognition—and their mathematical thinking skills, including recall, basic thinking, critical thinking, and creative thinking. It also investigated whether social awareness moderates the relationship between the teaching approach and both mathematical disposition and thinking skills. Additionally, the research aimed to assess the predictive power of mathematical disposition on mathematical thinking skills.